Kidney transplantation in highly sensitized patients: are there options to overcome a positive crossmatch? - Morath, Christian; Schmidt, Jan; Opelz, Gerhard; Zeier, Martin; Süsal, Caner (Langenbeck's archives of surgery, 2011)
Presensitization against a broad array of human leukocyte antigens (HLA) is associated with prolonged waiting times and inferior graft survival in kidney transplantation. Since the late 1960s, a positive lymphocytotoxic crossmatch has been considered a contraindication for kidney transplantation and solutions, such as enrollment of eligible patients in the Acceptable Mismatch Program of Eurotransplant and kidney paired donation in the case of living donor kidney transplantation, have been proposed to avoid this barrier. Alternatively, a positive crossmatch might not be considered as a contraindication for kidney transplantation and one can try to overcome this hurdle by desensitization. In principle, there are three different ways to overcome the crossmatch barrier by desensitization. The highly sensitized patient awaiting a cadaveric kidney transplant may be desensitized either immediately pretransplant when an organ is offered or in advance, during the time on the waiting list, to increase his chance of having a negative crossmatch at the time of transplantation. In the case of living donor kidney transplantation, the patient can be desensitized for days to weeks until the positive crossmatch with his intended living kidney donor becomes negative. “Heidelberg algorithm” is a combination of different measures, such as pretransplant risk estimation, good HLA match, inclusion of patients in the Eurotransplant Acceptable Mismatch program, and desensitization, which leads to timely transplantation and excellent survival rates in highly sensitized patients at a low rate of toxicity. We believe that all available options should be utilized in an integrated manner for the transplantation of kidney transplant recipients who are at a high risk of antibody-mediated rejection.